'Chinatown' and Global Operatic Knowledge. (July 2019) - Liao, Yvonne
Abstract : In recent years opera studies have taken a distinctly global and migratory turn: Nancy Rao's Chinatown Opera Theater is a notable example. Rao's book sheds new light on the art form's transpacific networks, Cantonese immigrant communities and their highly racialised experience of everyday entertainment in early twentieth-century America, thereby 'strip[ping] the veneer of exoticism from [southern] Chinese [i.e., Cantonese] opera, placing it firmly within the bounds of American music and a profoundly American experience'. Still more illuminating is Rao's focus on the Chinatown theatre companies, their contracting of touring performers and their role in transoceanic commerce. Woven into the book is an intimately connected narrative of Cantonese opera in the 1920s, encompassing San Francisco, Vancouver, New York, Honolulu and (to a lesser extent) Havana. The selection of these locations is no coincidence, given their significance in the interwar years as port cities linked within imperial steamship networks, amidst the part-conflicting, part-intersecting agenda of dominant and emergent empires (for instance, Japan and the United States, in the case of the latter).